GLOBAL ENVIRONMENTAL PROBLEMS AND THEIR EFFECTS FOR PEOPLE AND SOLUTIONS - Teshaboyeva Nafisa Zubaydulla qizi; Safarova Oydinoy Azizbek qizi (TADQIQOTLAR.UZ, 2024)
Annotation: Environmental issues happen due to disturbances in the normal functioning of the ecosystem. The various issues include climate change, environmental pollution, environmental degradation, and resource depletion. These types of environmental-related issues can occur either due to human causes or can be natural.They can vary in dimension from local, regional, to global levels. Environmental issues can be addressed by promoting green energy, recycling, conservation of water and electricity, and avoiding single-use plastic. In this environmental issues and solutions article, we will cover the various Environmental issues, the challenges presented by them, and their solutions.